Omalizumab beyond asthma (2012)
ABSTRACT: Introduction: Omalizumab has been demonstrated to be a successful therapy in the management of asthma through reduction of patient’s symptoms and use of inhaled corticosteroids. The effect of omalizumab is achieved by immunoglobulin E (IgE) blockage and other secondary mechanisms resulting from this blockage. Because other diseases have an important IgE mediation in their physiopathology, the question arises as to if omalizumab would be useful in the treatment of other IgE-mediated diseases. Objective: We present an overview of the experimental studies and clinical reports evaluating the use of omalizumab in diseases different to asthma including atopic dermatitis, urticaria, eosinophilic gastrointestinal disorders, idiopathic anaphylaxis, latex allergy, hymenoptera venom allergy, and other IgE diseases. Methods: We reviewed the literature using PUBMED, EMBASE, and LILACS for publications which used omalizumab in the treatment of patients with allergic diseases or any other diseases. Complete articles published in English, Spanish or Portuguese were included. Conclusion: There is not enough evidence to support the regular use of omalizumab in IgE diseases other than asthma. However, some experimental and clinical investigations indicate that omalizumab could be a therapeutic option in several allergic diseases like atopic dermatitis, urticaria, and eosinophilic gastrointestinal disorders. More control studies are needed in each IgE disease to evaluate the efficacy and safety of omalizumab in IgE mediated diseases.